Preserving the Rabbani Wahed Dance through Arts Extracurricular Activities: A Study of Cultural Digitalization - Umul Aiman; Novysa Basri (Gondang: Jurnal Seni dan Budaya, 2025)
This study aims to examine the preservation of Rabbani Wahed  Dance, a traditional dance originating from Bireuen District, Aceh, through arts extracurricular activities in junior high schools, as well as to explore its potential integration with digital technology. The research employed a qualitative method with an exploratory design, conducted at SMP Negeri 1 Bireuen, the only school that consistently teaches Rabbani Wahed  Dance through extracurricular programs. Data were collected through participatory observation, in-depth interviews, and documentation studies involving the school principal, cultural arts teachers, extracurricular instructors, students, local artists, and the Bireuen District Office of Education and Culture. The findings reveal that extracurricular activities of Rabbani Wahed  Dance function not only as a means of cultural preservation but also as a medium for character education, fostering students’ discipline, responsibility, and cooperation. Nevertheless, several challenges persist, including limited teacher competence, low student interest, lack of regeneration, and insufficient policy and funding support. Strategies that have been implemented, such as internal regeneration and principal support, remain inadequate to ensure the sustainability of the program. The utilization of digital technology holds great potential as an alternative learning resource, a documentation medium, and a platform for cultural promotion, thereby serving as a strategic solution to support the continuity of Rabbani Wahed  Dance in the modern era. This study highlights the urgency of formulating integrative preservation strategies that combine educational, cultural, and digital dimensions.